2011
DOI: 10.1021/jp1120299
|View full text |Cite
|
Sign up to set email alerts
|

On the Gelation of Graphene Oxide

Abstract: In the past half decade, graphene oxide (GO), a precursor of graphene, 1À4 has attracted a great deal of attention due to its unique structure and outstanding physical and chemical properties. 5À8 Particularly, GO behaves like an amphiphilic macromolecule with hydrophilic edges and a more hydrophobic basal plane, 9À11 which makes it an attractive building block for the construction of various supramolecular architectures. 12,13 Furthermore, the two-dimensional (2D) structure of GO sheets provides them with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
574
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 621 publications
(588 citation statements)
references
References 44 publications
13
574
1
Order By: Relevance
“…Water-soluble GO appears to be the ideal precursor for freeze casting. However, we found that directly freezing of GO dispersions only resulted in a randomly oriented porous structure, which is consistent with a previous report 34 . The monoliths directly resulted from unreduced GO displayed poor mechanical strength and small recoverable deformation region (Supplementary Methods).…”
Section: Resultssupporting
confidence: 93%
“…Water-soluble GO appears to be the ideal precursor for freeze casting. However, we found that directly freezing of GO dispersions only resulted in a randomly oriented porous structure, which is consistent with a previous report 34 . The monoliths directly resulted from unreduced GO displayed poor mechanical strength and small recoverable deformation region (Supplementary Methods).…”
Section: Resultssupporting
confidence: 93%
“…The arrangement of graphene sheets in solution/gel is attributed to the balance between electrostatic repulsion (originating from the functional group on the edge of graphene sheets) and interaction forces arising from hydrogen bonding and π-π interaction. 32,33 When the binding interaction is reinforced by filtration and becomes the main driving force, the graphene sheets in the gel tend to arrange a layered structure. Once the water was removed by air drying, the intersheet interaction could be further reinforced due to the partial flattening of the graphene sheets, forming a compact layered structure.…”
Section: Resultsmentioning
confidence: 99%
“…Critical analysis of the results do revel that the carbon nanowall growth evolution comprised: nucleation, growth and interconnection of graphite nanosheets onto nanoislands and subsequently coagulation of as-grown graphite nanosheets. They reported the highest CNW growth rate within the first 1-3 min, whereas a steady thickness was observed below 10 nm throughout the growth [38]. Furthermore, the OH radicals were vital during the initial nucleation stage, however , oxidation of the CNWs was observed if the OH radicals were in excess.…”
Section: Non-template Approachmentioning
confidence: 99%
“…Junhong Cheng and team [38] managed to highlight that with direct current plasma enhanced CVD and negative glow discharge, vertical graphene sheets can be grown on conductive substrates for instance Au and stainless steel. Vertical graphene patterns were designed by artificially designing the surface electric field distribution.…”
Section: Non-template Approachmentioning
confidence: 99%
See 1 more Smart Citation